Aspects of the foraging ecology of humpback whales (Megaptera novaeangliae) in Frederick Sound and Stephens Passage, Southeast Alaska - Szabo, Andrew R.
The North Pacific humpback whale (Megaptera novaeangliae) population has been increasing at an average annual rate of ~6% since the early 1990s. In northern Southeast Alaska alone, there are now more whales than estimated for the entire North Pacific several decades ago. An understanding of how this growing population is repopulating traditional foraging grounds will benefit from detailed investigations of their prey preferences and trends in whale abundance and distribution relative to those prey. This dissertation examines these issues from late May until early September 2008 in Frederick Sound and Stephens Passage, a Southeast Alaskan feeding area historically used by humpback whales. The foundation for the study is an analysis of the life histories and abundance patterns of euphausiids, the principal prey of humpbacks in the area, during late spring and summer. Four species, Thysanoessa raschii, T. longipes, T. spinifera, and Euphausia pacifica, were identified in plankton net samples collected at random locations throughout the study site (n = 49) and in locations where a strong scattering layer was observed on a 120 kHz echosounder (n = 48). Both sample types varied in euphausiid species composition. Abundance patterns of immature euphausiids coupled with observations of females carrying spermatophores indicated differences between species in spawning schedules. Thysanoessa spp. began spawning in early April with the spring phytoplankton bloom and continued until late June, whereas E. pacifica began spawning in early June and continued until late August. This protracted recruitment of immature euphausiids was geographically widespread throughout the summer in contrast to adults, which, although present all summer, were found primarily in slope and shallow (< 100 m) areas. To determine if humpback whales preferred one euphausiid species or life-stage over another, net sample and hydroacoustic data collected in the vicinity of whales were compared to similar data collected in random locations throughout ...